2018
DOI: 10.1507/endocrj.ej17-0399
|View full text |Cite
|
Sign up to set email alerts
|

Cullin-associated NEDD8-dissociated protein 1, a novel interactor of rabphilin-3A, deubiquitylates rabphilin-3A and regulates arginine vasopressin secretion in PC12 cells

Abstract: Abstract. The molecular mechanism involved in the exocytosis of arginine vasopressin (AVP) is not fully known. Rabphilin-3A has been suggested as a novel autoantigen in infundibulo-neurohypophysitis (LINH), which leads to central diabetes insipidus through insufficient secretion of AVP. However, the role of rabphilin-3A in the pathogenesis of LINH remains unclear. Thus, the aim of the present study was to identify proteins binding rabphilin-3A in the posterior pituitary. Using glutathione S-transferase (GST)-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Rabphilin-3A is a specific GTP-Rab3A-binding protein localized in secretory granules, where it regulates neurotransmitter release 47 50 . Regarding the involvement of rabphilin-3A in AVP secretion, AVP secretion was reported to be mediated by the interaction between rabphilin-3A and cullin-associated and neddylation-dissociated protein 1 51 . Rabphilin-3A may be a pathogenic antigen, and T cells specific for rabphilin-3A may be involved in the pathogenesis of neurohypophysitis in mice 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Rabphilin-3A is a specific GTP-Rab3A-binding protein localized in secretory granules, where it regulates neurotransmitter release 47 50 . Regarding the involvement of rabphilin-3A in AVP secretion, AVP secretion was reported to be mediated by the interaction between rabphilin-3A and cullin-associated and neddylation-dissociated protein 1 51 . Rabphilin-3A may be a pathogenic antigen, and T cells specific for rabphilin-3A may be involved in the pathogenesis of neurohypophysitis in mice 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it gave rise to clusters for more specific pituitary functions: genes with alternative splicing, prenylation, nuclear functions, and protein interactions ( Figure 7 B). For example, the “alternative splicing” cluster includes the pituitary-specific transcription factor Pou1f1 ( Pit1, see also Figure 6 A), essential for pituitary cell differentiation and transcription of prolactin and growth hormone [ 40 , 41 ], and Sequestosome 1 ( p62 ), essential for luteinizing hormone production [ 42 ], as well as the cullin-associated and neddylation-dissociated 2 ( Cand2 ) with a homolog Cand1 regulating vasopressin secretion [ 43 ]. Thus, the detected RISE-associated genes cluster for either basic or tissue-specific cellular functions depending on their regulation status by depolarization.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its interactors Smad2/3, Keap1-putdown interactome analysis also revealed that it may act as a key player in the process to sequentially add and remove ubiquitin by dynamic formation of distinctive functional complexes with ubiquitin conjugating enzymes (e.g., Cullin-1, 2, 3 , 4B, 5, ATG3, UBE3A, and UBE3C) and deubiquitinating enzymes (e.g., USP5, 7, 10, 12, 14, 15, 17L, 22, 24, 47 and UCHL5), as well as with cullin-associated NEDD8-dissociated protein 1 (CAND1, as an inhibitor promoting dissociation of substrate receptor components from the Cullin RING ligases 50 ). For this, it inferable that the selective dynamic formation of such opposite functional complexes is much likely to depend on distinctive tempo-spatial contexts of between Smad2/3 and Nrf2.…”
Section: Discussionmentioning
confidence: 99%